The psychotherapeutic role of the nurse in a psychodynamic unit - Gail Riccitelli (AOSIS, 1981)
A great deal has been written on the importance of therapeutic communities in the practise of psychiatry. This article proposes to highlight the extent to which the role of the psychiatric nurse has been developed in such a community. By considering aspects such as therapeutic dynamics, therapeutic intervention on an individual basis, group work and community work with specific reference to the nurse, attention will be drawn to the awvheon uise sw iwllhinicgh t ea rree loinpqeuni stho hthere rnouler saes, custodian and don the cloak of therapist.